Regulation of Progestin Receptors in Medial Amygdala: Estradiol, Phytoestrogens and Sex - Kudwa, AE (2009)
PHYSIOL BEH Exposure to estrogens during critical developmental periods and in adulthood affects sex differences in the brain. We examined the roles of estradiol (E2) and phytoestrogens, and their interactions, on potential sex differences in brain. We used aromatase knockout (ArKO) mice, which cannot produce endogenous estrogens, along with wild type (WT) littermates. Mice were gestated, raised and maintained on a diet either rich in phytoestrogens or a diet virtually void of soy-derived phytoestrogens. Adult males and females were gonadectomized and received implants filled with 17-β-estradiol to induce progestin receptors (PR), while controls received empty implants. Mice were sacrificed five days later and brain sections containing the posterodorsal medial amygdala (MePD) were processed for PR immunoreactivity. Activation of sex differences in PR required adult E2 treatment. A diet high in phytoestrogens was required for expression of sex differences in PR after E2 treatment. Our data underscore the important contribution of dietary phytoestrogens for the development of sex differences in PR-ir in the adult mouse medial amygdala. We hypothesize that both aromatization of androgens to estrogens and dietary sources of additional estrogens are part of the normal requirement for sex differences in the rodent brain.